Supragingival mycobiome and inter-kingdom interactions in dental caries. Issue 1 (1st January 2020) - Baraniya, Divyashri; Chen, Tsute; Nahar, Anubhav; Alakwaa, Fadhl; Hill, Jennifer; Tellez, Marisol; Ismail, Amid; Puri, Sumant; Al-Hebshi, Nezar Noor
ABSTRACT: Background : Recent studies have reveled the presence of a complex fungal community (mycobiome) in the oral cavity. However, the role of oral mycobiome in dental caries and its interaction with caries-associated bacteria is not yet clear. Methods : Whole-mouth supragingival plaque samples from 30 children (6–10 years old) with no caries, early caries, or advanced caries were sequenced for internal transcribed spacer 2 (ITS-2). The mycobiome profiles were correlated with previously published bacteriome counterparts. Interaction among selected fungal and bacterial species was assessed by co-culture or spent media experiments. Results : Fungal load was extremely low. Candida, Malassezia, Cryptococcus, and Trichoderma spp. were the most prevalent/abundant taxa. Advanced caries was associated with significantly higher fungal load and prevalence/abundance of Candida albicans. Cryptococcus neoformans and Candida sake were significantly over-abundant in early caries, while Malassezia globosa was significantly enriched in caries-free subjects. C. albicans correlated with Streptococcus mutans and Scardovia wiggsiae among other caries-associated bacteria, while M. globosa inversely correlated with caries-associated bacteria. In-vitro, M. globosa demonstrated inhibitory properties against S. mutans . Conclusions : the results substantiate the potential role of the oral mycobiome, primarily Candida species, in dental caries. Inter-kingdom correlations and inhibition of S. mutans by M. globosa are worth further investigation.